Réponses

2013-10-20T11:57:18+02:00
S= 7-13+2-(-14+6-3)
=7-13+2+14-6+3
=7

T=[-10,6-(0,6+1,2)]-(5,7-9,8)
=-10.6-0.6-1.2-5.7+9.8
=(9.8-1.2)-(10.6+0.6)-5.7
=8.6-11.2-5.7
= -8.3

U= -[5,5-(4,6-17,1)]-(12,6+4,9)
= -(5.5-4.6+17.1)-12.6-4.9
=-5.5+4.6-17.1-12.6-4.9
=-35.5
2013-10-20T12:31:30+02:00
S= 7-13+2-(-14+6-3)
7 -13 +2 +14 -6 +3
7 +2 +14 +3 -13 -6
+26 - 19 = +7

T= -10,6 - (0,6+1,2) - (5,7-9,8)
-10,6 - ( +1,8) -( - 4,1)
-10,6 -1,8 + 4,1
- 12,4 + 4,1 = - 8,3 

U= -(5,5-(4,6-17,1) - (12,6+4,9)
-(5.5)-( - 12,5 ) - (+17,5)
- 5.5 + 12,5 -17,5
-23 + 12,5 = -10,5